Being an Architect During World War I: Vedad (Tek) Bey’s Works for the Ministry of War - Müjde Dila Gümüş (Sanat Tarihi Yıllığı)
Mehmed Vedad (Tek) Bey undertook several essential tasks and roles during his career. Among these, he served as the Ministry of War's architect, which is particularly noteworthy as he held the post during the First World War. This era in Vedad Bey's career has not yet been the subject of detailed research. This article focuses on the architectural projects he prepared during his appointment at the Ministry of War, as well as his responsibilities in that position. Previous studies have shown that, between 1915 and 1918, Vedad Bey worked on various projects for the Seyr-i Sefain (Maritime) Administration. While Moda Pier, Haydarpaşa Pier, and the Seyr-i Sefain Agency were built, Kadıköy Pier remained unrealized. Vedad Bey's “third-class station” project, presented for the first time in this article, is examined in detail. The station, designed as a modest building in the Turkish National Style, was intended for the railway to be built between Ankara and Erzurum. Another project examined is the Enver Pasha Mansion of 1915. This structure is remarkable in terms of its divergence from contemporary architectural fashion with its round-arched and ionic column-headed entrance. Two other activities identified as undertaken by Vedad Bey for the Ministry of War are preparing comprehensive plans for the Veliefendi Hippodrome and his survey in Batumi to investigate the army's architectural requirements. It is thought that Vedad Bey also contributed to a military architecture handbook prepared in 1914. Accordingly, the architectural drawings in this book are explored briefly from a stylistic perspective.